ELECTRONIC VOTING: TO HAVE, OR NOT TO HAVE? - Matej Travnícek (European Scientific Journal, ESJ, 2014)
This article focuses on various factors related to electronic voting. The analysis therefore concerns formal requirements for electoral process, counting speed, number of invalid votes, counting errors, trust and electoral frauds, accessibility of the elections and turnout. In the finale the impact of e-voting is summarized and recommendation is delivered. The findings indicate that electronic voting can solve some problems in electoral design, but as well can deepen the existing ones and even create a new ones. It is therefore important to discuss it in context of respective electoral design, because there is no universal answer to the question contained in the name of the article.